Syndromes and a century = Sang sattawat - Anantagant, Kantee ca. 20. Jh (British Film Institute, 2008)
"[...] This, his fifth feature, is a spellbinding Buddhist meditation on the mysteries of love and attraction, the workings of memory, and the ways in which happiness is triggered. Dubbed "a hospital comedy of a metaphysical bent", it features young doctors in love, a Buddhist monk who suffers from bad dreams about chickens, an elderly haematologist who hides her whisky supplies in a prosthetic limb, and a young monk who forms an intense bond with a singing dentist." [bfi.org.uk]
Bildformat 1.66:1 (16:9 anamorph)
Orig.: Thailand/Österreich/Frankreich, 2006
Enth. interview with director (15 mins) ; "Worldly desires": an experimental love story (Weerasethakul, 2005, 40 mins.) ; original trailer ; illustrated booklet with production stills, location drawings, etc.
Keywords: Krankenhaus; Zwischenmenschliche Beziehung; Wiedergeburt; Thailand; DVD-Video